Desenvolvimento e produtividade do algodoeiro em função de espaçamentos e aplicação de regulador de crescimento - Ferrari, Samuel [UNESP]; Furlani Júnior, Enes [UNESP]; Ferrari, João Vitor [UNESP]; Santos, Marcio Lustosa [UNESP]; dos Santos, Danilo Marcelo Aires [UNESP] (My University, 2008)
Currently, the cultivation of the cotton plant is based on a scale production model, characterized by high yields and intensive use of fertilizers, agrochemicals and mechanization. The objective of this study was to evaluate the influence of different row spacings on cotton crops, with or without growth regulator, and their effects in crop development and yield. The experimental design was in completely randomized blocks, in a 3×3 factorial scheme with 4 replications, using three row spacings: 0.45, 0.70 and 0.90 m. Three growth regulator conditions were tested: a) application split into four stages, b) single application at 70 d.a.e, and c) no regulator application. The project was conducted in the city of Selvíria, Mato Grosso do Sul state, in November 2005. It was verified that the application of growth regulator is efficient in the limitation of plant height. The highest yield and boll mass was found in the split application of the regulator. The number of bolls and reproductive branches per plant was higher in the wider row spacings.
Development and yield of the cotton plant under different row spacings and growth regulator application
Keywords: Agronomic characteristics; Mepiquat chloride; Plant density; Yield